(untitled) (Bangladesh Journal of Medical Science, 2018)
Back Ground: Diabetes mellitus is a group of metabolic disease with high blood glucose level above 150 mg/dL over a prolonged period. The elevated of blood glucose, free fatty acid and insulin resistance will cause the endothelial dysfunction, hemostasis disturbances that lead to micro and macrovascular complications. Poguntano (Picria fel-terrae Merr) from family Scrophulariaceae found in most part of Indonesia, has been used as traditional plant for treatment of diabetes. Objective: The purpose of this study was to investigate the effect of extract ethanol of Poguntano in alloxan induced diabetic rats. Method: Fifteen male Wistar rats with body weight of 150-200 gr were given intra peritoneal injection of 150 mg/kg Alloxan to induce diabetes. These were divided into three groups (control diabetic, group given insulin and group given Extract ethanol of Poguntano 200 mg/Kg body weight) and one control normal control. The duration of study was 4 weeks; blood glucose and Endothelin-1 were measured for all groups. Results : Extract ethanol of Poguntano 200 mg showed significant results (p<0.001) in lowering blood glucose in Alloxan induced diabetic rats compared to control diabetic, but did not show superior to insulin group (p=0.892). Endothelin-1 showed statistical significant between group with normal rats and diabetic control rats. (p=0.009) but did not in the other groups. Levels of Endothelin-1 was higher in the diabetic control group with the median 1.95 (1,78- 3.1). Conclusion: In our study we found that extract ethanol of Poguntano showed significant hypoglycemic activity and lowering the Endothelin-1 level in alloxan induced diabetic rats. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.251-254